What kind of effects had the global economic crisis on the attendance of the NBA games? - Váczi, Péter (Applied Studies in Agribusiness and Commerce, 2013)
The global economic crisis of 2008 had effects on the world at all levels of life. It caused serious problems and difficulties in professional sports as well. In my paper I will try to show what kind of effects the global economic crisis had on one of the best organised championships of the world. What effects it had on attendance? How this influenced the prices of the tickets to the matches?I am going to show those marketing and financial steps, which were made by the championship’s leader corp and the teams participating in it. I think the teams could moderate their losses by making different special offers, drafting new players and being opened for the foreign countries, I think this will lead to an increase in attendance in the next few years. Finally, I will try to make a future forecast of attendance.